Antidiabetic potential of Lantana aculeata root extract in alloxan-induced diabetic rats - K. Vinoth Kumar; S. Dawood Sharief; R. Rajkumar; B. Ilango; E. Sukumar (International Journal of Phytomedicine, 2010)
The present study investigates the antidiabetic potential of dried mature roots of Lantana aculeata, a weed belonging to verbenaceae family on biochemical profile in alloxan-induced diabetic rats. The effects of an ethanolic extract of the dried mature roots of Lantana aculeata on serum glucose, total cholesterol, triglycerides, plasma insulin and liver glycogen were examined in control and experimental groups. Lantana aculeata root extract reduced the serum glucose concentration at 24, 48 and 72 hours. To verify the activity sub-chronically, the extract administered orally in the doses of 25, 50 and 100 mg/kg to diabetic rats for 30 days, that significantly reduced the level of glucose, total cholesterol and triglycerides with an increase in insulin and glycogen concentration to near normal levels in a dose-dependent manner. The results indicate that roots of Lantana aculeata possess antidiabetic potential in alloxan-induced diabetic rats. The activity might be due to high concentration of oleanolic acid present in the roots.